2005
DOI: 10.1007/s00438-005-1129-6
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis mutant that is resistant to the protoporphyrinogen oxidase inhibitor acifluorfen shows regulatory changes in tetrapyrrole biosynthesis

Abstract: Several Arabidopsis mutants of the ecotype Dijon were isolated that show resistance to the herbicide acifluorfen, which inactivates protoporphyrinogen oxidase (PPOX), an enzyme of tetrapyrrole biosynthesis. This enzyme provides protoporphyrin for both Mg chelatase and ferrochelatase at the branchpoint, which leads to chlorophyll and heme, respectively. One of the mutations, aci5-3, displays semidominant inheritance. Heterozygous progeny showed yellow-green leaves, while the homozygous seedlings were white and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 38 publications
3
30
1
Order By: Relevance
“…We recently investigated the aci5 mutant of A. thaliana (Soldatova et al 2005), which was obtained by chemical mutagenesis and further selection for resistance to aciXuorfen, an inhibitor of protoporphyrinogen oxidase, the enzyme preceding Mg chelatase in the chlorophyll biosynthetic pathway (Ezhova et al 2001). The mutant gene identiWed by genetic mapping and sequence analysis encodes CHLI 1.…”
Section: Introductionmentioning
confidence: 99%
“…We recently investigated the aci5 mutant of A. thaliana (Soldatova et al 2005), which was obtained by chemical mutagenesis and further selection for resistance to aciXuorfen, an inhibitor of protoporphyrinogen oxidase, the enzyme preceding Mg chelatase in the chlorophyll biosynthetic pathway (Ezhova et al 2001). The mutant gene identiWed by genetic mapping and sequence analysis encodes CHLI 1.…”
Section: Introductionmentioning
confidence: 99%
“…Data from three recombinant plants delimited the cs215 locus to the region encompassed by bacterial artificial chromosomes F28J12 and F28A21. One of the genes in this region, At4g18480 encoding CHLI1, has been shown to have mutant alleles with semidominant pale-green phenotypes (Kjemtrup et al, 1998;Fitzmaurice et al, 1999;Hansson et al, 2002;Soldatova et al, 2005). Therefore, we sequenced the region of At4g18480 from cs215 and found that cs215 indeed had a C-to-T mutation at nucleotide 584 that converted a Thr at residue 195 to an Ile (Fig.…”
Section: Identification Of the Cs215 Locusmentioning
confidence: 99%
“…In the cs215 mutant, the high amount of cs215 mutant protein may out-compete the low amount of CHLI2 in assembly with CHLD. It is also possible that the expression levels of CHLI1 and CHLI2 were similar (Rissler et al, 2002;Apchelimov et al, 2007) and that the presence of the cs215 mutant protein inhibited the expression of CHLI2 as suggested previously (Soldatova et al, 2005). To clarify the role of CHLI2, we compared the expression levels of CHLI1 and CHLI2 using realtime quantitative RT-PCR.…”
Section: Chli2 Supports Some Chlorophyll Biosynthesis In the Absence mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the four preceding enzymatic steps ( Figure 1A), reduced Mg-chelatase activity does not cause photosensitivity, but rather reduced chlorophyll levels due to a negative feedback regulatory mechanism (Hansson et al, 1999(Hansson et al, , 2002Papenbrock et al, 2000aPapenbrock et al, , 2000bSoldatova et al, 2005;Sawers et al, 2006). The substrate of Mg-chelatase, protoporphyrin IX, is the branch point of chlorophyll and heme synthesis ( Figure 1A); by contrast, antisense suppression of the first committed heme synthetic enzyme, plastidic ferrochelatase, does lead to protoporphyrin IX accumulation and light-dependent necrosis (Papenbrock et al, 2001).…”
Section: Discussionmentioning
confidence: 99%